2009
DOI: 10.1158/1535-7163.mct-08-0927
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytokine-induced macrophages on the response of tumor cells to banoxantrone (AQ4N)

Abstract: Tumor-associated macrophages (TAMs) are found in many solid tumors and have often been shown to accumulate in the hypoxic regions surrounding areas of necrosis. TAMs are the major site of expression of nitric oxide synthase (NOS), a heme-containing homodimeric enzyme consisting of oxygenase and reductase domains. The latter has a high degree of sequence homology to cytochrome P450 reductase and a functional consequence of this is the ability of NOS, under hypoxic conditions, to activate the bioreductive drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
(50 reference statements)
2
23
0
Order By: Relevance
“…A number of studies have shown that cytochrome P450 enzymes (CYP) and other haem-containing reductases, suchas nitric oxide synthase, contribute to the bioreduction of AQ4N under anoxic conditions (16)(17)(18). The ability of S9 or microsome fractions to activate AQ4N to AQ4 ex vivo has been shown in human liver microsomes (16), activated macrophages (18), and murine tumors (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown that cytochrome P450 enzymes (CYP) and other haem-containing reductases, suchas nitric oxide synthase, contribute to the bioreduction of AQ4N under anoxic conditions (16)(17)(18). The ability of S9 or microsome fractions to activate AQ4N to AQ4 ex vivo has been shown in human liver microsomes (16), activated macrophages (18), and murine tumors (19).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of S9 or microsome fractions to activate AQ4N to AQ4 ex vivo has been shown in human liver microsomes (16), activated macrophages (18), and murine tumors (19). Recent work has shown that AQ4N can be activated in vivo in tumor xenograft samples (3,20), and in clinical samples from a phase I study (12).…”
Section: Introductionmentioning
confidence: 99%
“…BxPC-3 cells are intrinsically sensitive to the active metabolite AQ4 in vitro, and they respond favorably to AQ4N when grown as solid tumors in vivo (Lalani et al, 2007), indicating that AQ4N activation is not deficient in BxPC-3 tumors in vivo, in contrast to our findings in culture. Conceivably, enzymes active in AQ4N bioactivation, such as cytochromes P450 2S1 and 2W1 (Nishida et al, 2010), might be more highly expressed in the context of the tumor environment in vivo; alternatively, AQ4N activation might occur in tumorassociated host cells such as macrophages, which have the capacity to activate AQ4N by iNOS (Mehibel et al, 2009). Conversely, whereas cultured 9L cells responded well to AQ4N, the 9L tumor xenografts were largely unresponsive (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Certain cytochrome P450 enzymes (McErlane et al, 2005;Nishida et al, 2010;Xiao et al, 2011) and iNOS (Fitzpatrick et al, 2008;Nishida and Ortiz de Montellano, 2008;Mehibel et al, 2009) can activate AQ4N via a two-step reduction of the di-N-oxide to the di-amino compound AQ4. Other pathways of reductive metabolism demonstrated for related quinones include one-electron reduction to a semiquinone radical and two-electron reduction to a hydroquinone, both of which can be cytotoxic (Nguyen and Gutierrez, 1990;Ross et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation